Analysis of interannual variability of sunshine hours and precipitation over Peninsular Spain. (November 2015) - Gil, Victoria; Gaertner, Miguel A.; Sanchez, Enrique; Gallardo, Clemente; Hagel, Edit; Tejeda, Cesar; de Castro, Manuel
Abstract: Solar energy is one of the more abundant sources of renewable energy. It would be desirable that it is more stable over time than other energies with high interannual variability like hydropower. In this study we analyse the interannual variability of sunshine hours and precipitation over Spain, with the aim of comparing the reliability of solar energy to hydropower. An analysis in this respect has not been done before. We have used data from almost 100 stations in the WMO–AEMET (Spanish State Agency for Meteorology) network, and have applied two indices, the coefficient of variability (CV) and the speed of convergence, defined as the number of years of data needed to fully characterize a site. The main result is that the interannual variability for sunshine hours is several times lower than for precipitation over most of Spain, with the exception of the northern coast. The southwestern peninsular area stands out in this respect. This area is characterized at the same time by the highest number of sunshine hours, high speed of convergence and a low maximum departure of annual sunshine hours from the long-term mean. All this make this area optimal and very reliable for placing solar power plants. Highlights: Interannual variability for sunshine hours is lower than for precipitation. Low variability and many sunshine hours do not imply low rainfall. Annual values of CV are similar to the lowest monthly value. Stations with minimum CV have a high speed of convergence. The southwest of Iberian Peninsula is an ideal zone for solar thermal power plants.